The hen house - Ahlberg, Allan; Amstutz, André (illustrator) (London, Viking.Puffin, 1999)
It is bedtime in the Hen House and Mother Hen, Slow Dog and the chickens are getting ready for bed, but a sinister character lurks in the shadows. The intruder abducts the chickens, but luckily, Slow Dog sleepwalks out of the window and lands on the intruder, who turns out to be Fast Fox.